Performance evaluation of rare earth (La, Ce and Y) modified CoFe2O4 oxygen carriers in chemical looping hydrogen generation from hydrogen-rich syngas. (15th October 2022) - Gao, Jie; Pu, Ge; Yuan, Cong; Gao, Mengliang; Lu, Xingqiang; Jia, Shuaihui
Highlights: The CL-CCHG process was proposed to purify multi-component hydrogen-rich syngas. Rare earth (especially La) modified CoFe2 O4 exhibited superior CLHG properties. Competitive effects among components and temperature correlation were investigated. The La0.1-CoFe had the highest hydrogen recovery efficiency of 90.38 % at 800 °C. High-purity (˃ 99.5%) H2 recovery was achieved along with efficient CO2 capture. Abstract: In this study, chemical looping cascade coupling hydrogen generation (CL-CCHG) process was proposed to achieve conversion from multi-component hydrogen-rich syngas to high purity hydrogen. CLHG experiments using simulated methane reforming gas (MRG, 64.89 % H2  + 24.47 % CO + 7.18 % CO2  + 3.46 % CH4 ) were carried out on a self-built fixed bed reactor to verify the feasibility of this process, and rare earth (La, Ce and Y) modified CoFe2 O4 was selected as oxygen carriers. The crystal structure, surface morphology and properties, and reactivity of oxygen carriers were characterized by various analytical methods (e.g., XRD, SEM-EDS, BET, XPS, TPR). The fixed bed experimental results exhibited that rare earth modification significantly improved the fuel conversion capacity, carbon capture efficiency and hydrogen production capacity of CoFe2 O4, with La0.1-CoFe possessing the highest overall fuel conversion rate (85.97 %) and hydrogen recovery efficiency (89.46 %) at 750 °C. This was attributed to the enhanced pore structure, surface properties and reduction performance of oxygen carriers after the rare earth modification. Moreover, experimental results and HSC thermodynamic data demonstrated that the reducing components showed different competing effects in the temperature range examined (650–850 °C). The high temperatures favored the conversion of low concentrations CH4 in MRG, but this would inhibit the consumption of CO and H2 . The reduced La0.1-CoFe oxygen carrier achieved the best hydrogen production intensity at 800 °C (302.91 vs 335.15 mL H2 ·g −1 OC) with hydrogen recovery efficiency of 90.38 %. Finally, by adjusting the MRG flow rate, 94.36 % carbon capture efficiency was obtained, achieving efficient recovery of high purity hydrogen (>99.5 %) along with carbon capture.